Immersive Environment with Virtual Reality and Eyetracking in the Public Sector: Modernization of the TCE-GO Server onboarding and Training Process - Lima, Leonardo Oliveira; Nascimento, Jaqueline Gonçalvez do; Deniz, Pedro Koziel; Vieira, Judson Luiz Paz; Andrade, Carolina Horta; Silva, Meryck F. B. da (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais Estendidos do XXVII Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2025.15789, 2025)
The combination of virtual reality (VR) and biofeedback technologies, such as eye tracking, offers new possibilities for measuring user presence and attentional focus in immersive environments. In the context of institutional training, this synergy proves particularly promising. This study presents a proposed VR-based onboarding and training platform for new employees of the Court of Accounts of the State of Goiás (TCE-GO), with a focus on visual attention measurement. By employing 3D modeling, integration with eye tracking technology, and data analysis through AI models, the project aims not only to familiarize new employees with the court’s workflows but also to train technical skills and objectively assess their levels of engagement. The research is grounded in the Design Science Research (DSR) methodology, encompassing the design and development of the onboarding environment. Expected outcomes include increased efficiency and scalability in the training process, as well as a pioneering application of VR and biofeedback in employee training for Courts of Accounts.